Molecular Drug Design, Synthesis and Antibacterial study of Novel 4-Oxothiazolidin-3-yl Derivatives - Sarah S. Ismaeel; Monther F. Mahdi; Basma M. Abd Razik (College of Pharmacy / Mustansiriyah University, 2020)
New compounds containing 4-thiazolidinone pharmacophore 5(a) and (5b) have been synthesized. The chemical structures of the intermediate and final compounds were characterized and confirmed by using FT-IR and 1H-NMR spectroscopy. All final compounds were tested against gram-positive and gram-negative bacteria using a well-diffusion technique for their ability as antimicrobial agents.  The tested compounds 5a and 5b showed variable and modest antibacterial activity against gram-negative bacteria and gram-positive bacteria. Molecular docking simulations were studied to understand the molecular core. The results were achieved by docking, the most active compounds into the active site of protein of the bacteria which completely accorded with in vitro results.